Involvement of Transposon-Like Elements in Penicillin Gene Cluster Regulation - Shaaban, Mona (2010)
Subtelomeric secondary metabolite (SM) gene clusters are frequently surrounded by DNA repeats and transposon-like elements. The A. nidulans penicillin cluster, 30 kb from the telomere of chromosome VI, is bordered by such elements. Deletions of penicillin telomere proximal and distal border regions resulted in decreased penicillin production. A 3.7 kb distal region called PbIa, consisting of the putative transposable element DNA-2, was examined further where its replacement by a pyrG marker presented a similar phenotype as loss of the global SM regulator LaeA, resulting in a decrease in penicillin gene expression and product formation. In contrast, placement of the pyrG marker on either side of PbIa had no effect on penicillin synthesis. A requirement for PbIa in penicillin production was also apparent in a histone deacetylase mutant, ΔhdaA, enhanced for penicillin production. Trans complementation of the PbIa element near and within the terrequinone A cluster on chromosome V did not restore penicillin biosynthesis or increase production of terrequinone A. Taken together, this data provides evidence for transposon involvement in SM cluster regulation.